Optimasi Distribusi Kayu Rakyat di Wilayah Kabupaten Ciamis - Muhammad Resta Destyana; Hardjanto; Tatang Tiryana (Jurnal Penelitian Pendidikan IPA, 2025)
Private timber distribution in Ciamis faces efficiency challenges due to high operational costs, limited spatial information, and middleman dominance in the supply chain. This study aims to (1) identify timber trade institutions, (2) determine spatially optimal distribution routes, and (3) design an efficient distribution model. Methods include institutional surveys, slope- and elevation-based spatial analysis, and Linear Programming optimization via Excel Solver. Results show that optimal routes combine high safety percentages (88.27% recommended routes) with minimal transportation costs. The optimization model increased profit by IDR 32.17 million/month while reducing operational costs by 1.45%. This integrated spatial-optimization approach enhances logistical efficiency and supports sustainable private forest management.